South–South cooperation and the geographies of Latin America–Caribbean integration and development: a socio-spatial approach - Muhr, Thomas (Wiley, 2016)
Structured around the case of South–South cooperation in the construction of “complementary economic zones” among the member states of the ALBA-TCP, Petrocaribe, CARICOM and MERCOSUR, this article argues for a socio-spatial approach to the study of the Latin America–Caribbean integration and development. Two interrelated arguments are developed: first, in contrast to methodologically nationalist approaches, which typically view the regionalisms that are to form the complementary economic zones as ideologically separate, incompatible or conflicting projects, a sociospatial approach in conjunction with a South–South cooperation analytical lens explains their commonality and, subsequently, their interrelatedness and convergence. Second, while this South–South cooperation space is not per se non-capitalist, a socio-spatial analysis also facilitates “seeing” the production of a socialist “counter-space” within this South–South cooperation structure.